Acute and chronic airway obstruction in children. Issue 1 (January 2019) - Armstrong, Earlene E.; Bell, Graham
Abstract: Airway management is one of the fundamental skills of any anaesthetist. Considerable anatomical changes occur between birth and adulthood during the development of the paediatric airway. Knowledge of these changes will influence airway planning during childhood. Airway obstruction complicates airway management and any anaesthetist working with children should be able to assess the airway for the presence of obstruction and generate a differential diagnosis of cause. This article aims to summarize key anatomical features of the paediatric airway, common causes of airway obstruction in children and provide suggestions for how to manage these patients.